Model Pembelajaran Kooperatif Tipe Think Pair Share Berbantuan Video Pembelajaran Materi Relasi Dan Fungsi - Sauwera, Arpina; Zakaria, Perry; Machmud, Tedy; Ismail, Yamin; Isa, Dewi Rahmawaty (Scimadly Publishing, 2023)
This research aims to determine the effect of the think pair share type cooperative learning model assisted by educational videos on student learning outcomes in relation and function material. The research was carried out in SMP Negeri 1 Suwawa in the alternate semester of the 2022/2023 academic year. The population in this study was all class VIII, totaling 83 people. The sample used was 20 students in the experimental class and 20 students in the control class. The research results show a significant difference in the average learning outcomes of students who study using the think pair share cooperative learning model, which is higher than the direct learning model.